HEAT TRANSFER ENHANCEMENT IN A DOUBLE PIPE GEOTHERMAL WELL - DAVE, NAVIN (IRC, 2018)
In this paper, abandoned oil wells are being simulated to act as a heat exchanger. The heat source comes from the geothermal energy which is available in abundance around the oil wells that comes from the strata rock. Because it is a seemingly endless resource, it could be capable of replacing other forms of energy sources if it is used correctly. Geothermal energy extraction from abandoned oil wells is one of the new ways to take advantage of the under-utilized geothermal energy, this is carried out using the double pipe heat exchanger mechanism. A model of the 4km depth well bore is presented. The working fluid in this case is chosen to be water and simulated throughout this project. Numerical simulation for the well bore is carried out. After, various modifications are done upon the well in order to further increase the temperature of the water outlet at the well. The purpose of this paper is to propose one of the best solutions in increasing the temperature outlet as much as possible. Using simulation, various ways to increase the temperature are carried out and the most viable option will be chosen at the end of the project.